2020
DOI: 10.1039/d0cc06093c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of pressure swing regeneration for faster cycling in sorption enhanced dimethyl ether synthesis

Abstract: Sorption enhanced dimethyl ether synthesis (SEDMES) is a novel DME production route from CO2-rich feedstocks. In situ water removal by adsorption results in high single-pass conversions, thereby circumventing the disadvantages...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Although several routes exist and are currently in operation for the industrial synthesis of DME (Müller and Hübsch, 2000;Azizi et al, 2014), separation-enhanced synthesis routes have shown to offer major advantages in the conversion of carbon dioxide to chemicals . In fact, sorptionenhanced DME synthesis (SEDMES) has proven to yield a very high single-pass carbon selectivity to DME (Iliuta et al, 2011;van Kampen et al, 2020a;van Kampen et al, 2020b;van Kampen et al, 2020c). In this novel technology, steam is adsorbed in situ to overcome the thermodynamic limits of the reactions involved, resulting in the high single-pass DME yield.…”
Section: Introductionmentioning
confidence: 99%
“…Although several routes exist and are currently in operation for the industrial synthesis of DME (Müller and Hübsch, 2000;Azizi et al, 2014), separation-enhanced synthesis routes have shown to offer major advantages in the conversion of carbon dioxide to chemicals . In fact, sorptionenhanced DME synthesis (SEDMES) has proven to yield a very high single-pass carbon selectivity to DME (Iliuta et al, 2011;van Kampen et al, 2020a;van Kampen et al, 2020b;van Kampen et al, 2020c). In this novel technology, steam is adsorbed in situ to overcome the thermodynamic limits of the reactions involved, resulting in the high single-pass DME yield.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the macropore diameter would be a factor ten smaller (0.1 μm), the micropore resistance would make up more than 95% of the 8 GSTA model prediction (line) for low temperature data at a partial pressure of 2.337 kPa from Ghodhbene et al (Ghodhbene et al 2017) total mass transfer resistance. Also the practical adsorbent pellet size can vary, affecting the external film resistance and mainly the macropore resistance due to the quadratic dependence, which has been shown to influence the overall mass transfer coefficient significantly (Simo et al 2009;Terreni et al 2018). Experiments with varying pellet size would clarify the relative contribution of the different mass transfer resistances.…”
Section: Adsorbate Mass Transfermentioning
confidence: 99%
“…Experiments with varying pellet size would clarify the relative contribution of the different mass transfer resistances. In addition, direct imaging could be a powerful technique to circumvent possible issues arising from this, and is a good addition to the existing experimental methods (Terreni et al 2018;Sircar 2007). As shown by the difference between the graphs in Fig.…”
Section: Adsorbate Mass Transfermentioning
confidence: 99%
See 2 more Smart Citations